Exploring the Ability of Early Childhood Teachers to Carry Out Assessment - Anita Yus; Dwi Septi Anjas Wulan; Winda Widya Sari; Salim Salim (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to determine how the application of authentic assessment in kindergarten by assessing the adequacy of aspects of assessment and implementation of assessment instruments. Research respondents are kindergarten teachers in North Sumatra Province, totaling 65 people. The data was collected using a questionnaire and document analysis, which consisted of lesson plans, children's work that had been analyzed by the teacher and the assessment instruments that had been used by the teacher. Data were analyzed using descriptive statistical techniques and qualitative analysis by linking existing data to obtain meaning. The results of the analysis showed that: (1) there were 100% of kindergarten teachers who stated that they had carried out an assessment every time they carried out the teaching process but most had difficulty indicating the assessment instrument used, (2) 97% of kindergarten teachers only used a checklist to collect developmental assessment data and children's learning activities by putting a check mark on one of the scales consisting of "developing very well", "developing as expected", "starting to develop", and "not developing", (3) 98% of kindergarten teachers use the instruments in the book assessment guide issued by the government and have never used an assessment rubric developed by the teacher to determine child development achievements, and (4) 89% of kindergarten teachers do not collect assessment data in the context of competencies being developed, (5) kindergarten teachers have difficulty using descriptive notes or class notes to record the child's behavior during the teaching process due to difficulties in to write down the child's behavior as seen by the teacher, and (6) as many as 89% of kindergarten teachers have not used an assessment instrument developed based on the principles of authentic assessment. The results of this study have implications for the need to develop an assessment model that is useful to help teachers conduct a valid and reliable assessment of child development.